Evolution of the human brain : from matter to mind - Hofman, M. A. (Michel A.) (Progress in brain research ;, 2019)
"Evolution of the Human Brain: From Matter to Mind, Volume 250 in the Progress in Brain Research, series documents the latest developments and insights about the origin and evolution of the human brain and mind. Specific sections in this new release include Evolution and development of the human cerebral cortex, Functional connectivity of the human cerebral cortex, Lateralization of the human cerebral cortex, Life history strategies and the human cerebral cortex, Evolution of the modern human brain, On the nature and evolution of the human mind, Origin and evolution of human cognition, Origin and evolution of human consciousness, and more."--Publisher's web page, viewed November 7, 2019